2018
DOI: 10.1029/2018wr022767
|View full text |Cite
|
Sign up to set email alerts
|

When Should Irrigators Invest in More Water‐Efficient Technologies as an Adaptation to Climate Change?

Abstract: The western U.S. is expected to experience more frequent and severe droughts as a result of climate change, with potentially large impacts on agricultural production and the economy. Irrigated farmers have multiple options for minimizing the impact of drought including switching to more efficient irrigation technologies. More efficient technologies that increase the fraction of the water available to the crop root zone would allow farmers to maintain current production levels with less water. However, these sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 118 publications
0
22
0
Order By: Relevance
“…The capabilities of YAK-RW, on the other hand, allow us to reasonably simulate impacts of water rights and the operation of water facilities. A comprehensive description of all of the components of the simulation tools used in this study can be found in Malek et al 14 .
Fig.
…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The capabilities of YAK-RW, on the other hand, allow us to reasonably simulate impacts of water rights and the operation of water facilities. A comprehensive description of all of the components of the simulation tools used in this study can be found in Malek et al 14 .
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we focus on the Yakima River Basin (YRB; Supplementary Fig. 1 ), an agriculturally important and heavily irrigated snow-dependent river basin 13 , 14 in the Pacific Northwest of the US. Background on the YRB, including its regional context, and water rights structure can be found in the method section.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regional application of VIC-CropSyst in conjunction with a river system model (YAK-RW; Hubble, 2012;Zagona et al, 2001) and an economic model to simulate historical drought frequency (a), when the percentage of the water allocated for the irrigation season (i.e., proration rate) is lower than 70, 80, and 90 %. Panels (b) and (c) (Malek et al, 2017b) show the percentage of farmers (perennial crop growers) who invest in new efficient irrigation technologies in response to simulated droughts during the two decades of 1990-2000 (b) and 2050-2060 (c).…”
Section: Foundation For Integration Within Other Modeling Platformsmentioning
confidence: 99%
“…Therefore, their impacts on water systems are of great concern to hydrologists and water managers alike. Over the past years, numerous climate impact studies have been launched to assess possible changes to hydrologic responses as a result of climate changes and their effects on human societies (Malek et al, 2018; Mekonnen et al, 2018; Pulido‐Velazquez et al, 2018; Roy et al, 2018; Yang et al, 2019). These studies mainly use two alternative approaches, top‐down and bottom‐up, as explained by Wilby and Dessai (2010) and Blöschl et al (2013).…”
Section: Introductionmentioning
confidence: 99%